Blunt cerebrovascular injury in rugby and other contact sports: case report and review of the literature - Cuellar, Trajan A (BioMed Central, 2014)
Contact sports have long been a part of human existence. The two earliest recorded organized contact games, both of which still exist, include Royal Shrovetide Football played since the 12(th) century in England and Caid played since 1308 AD in Ireland. Rugby is the premier contact sport played throughout the world with the very popular derivative American football being the premier contact sport of the North American continent. American football in the USA has on average 1,205,037 players at the high school and collegiate level per year while rugby in the USA boasts a playing enrollment of 457,983 at all levels. Recent media have highlighted injury in the context of competitive contact sports including their long-term sequelae such as chronic traumatic encephalopathy (CTE) that had previously been underappreciated. Blunt cerebrovascular injury (BCVI) has become a recognized injury pattern for trauma; however, a paucity of data regarding this injury can be found in the sports trauma literature. We present a case of an international level scrum-half playing Rugby Union at club level for a local non-professional team, in which a player sustained a fatal BCVI followed by a discussion of the literature surrounding sport related BCVI.